PERFORMANCE ANALYSIS AND IMPROVEMENT RECOMMENDATIONS OF LIPI PRESS OFFICIAL WEBSITE - Kushadiani, Siti Kania; Perdananugraha, Gonang May (LIPI Press, 2014)
LIPI Press official website, penerbit.lipi.go.id, provides hundreds of data catalogs of scientific publications. When referring to the site as a provider of publications catalog, the website has weakness and do not follow thedevelopment of web technology. In this paper, analysis of the website was conducted by using eight (8) web analyzer namely WooRank, Seoptimer, Lipperhey, iWebChk, SEO Workers, Sailor SEO, SEO Site Checkup, and SEOAnalyzer. The results showed that the six web analyzers provide low valuation on the site and only 2 other web analyzers provide medium valuation.